Corporate governance attributes, banks characteristics and green banking disclosure in Indonesia - Yulia, Yulia; Muhammad, Rafiuddin; Rokiah, Paee (Universitas Islam Negeri (UIN) Walisongo, 2025)
Purpose - The purpose of this study is to examine the influence of corporate governance attributes and banks characteristic on Green Banking Disclosure of Indonesian Islamic banks.